Calidad organoléptica y fisicoquímica de una pasta dentífrica y de un gel dental elaborados a base de miel de abejas procedente de montoya – ichocán – cajamarca. (septiembre 2010). - Pasco Olguín, Gary Alexánder (2010)
The study had as objectives: Elaborating a tooth paste and a dental gel as the basic ingredients honey of bees as beginning active, evaluate the organoleptic characteristics and physicochemistries of both elaborate products as the basic ingredients honey of bees and compare the characteristics of quality between both cosmetic products. For investigation happiness, carried out the characterization of the reasonable honey of Montoya, province of Ichocán, Cajamarca-Peru; with she who then it is elaborated a tooth paste and a dental gel, by using a concentration of 7 %, minimum concentration bactericide of the honey in study on Streptococcus mutans. Afterwards carried out the controls of quality: organoleptic (aspect, color, relative consistency, smell, flavor and evaluation of sensation when applying) and physicochemistries (viscosity, acidity of level and trials of stability). With this work of investigation it reaches to the following conclusions: the honey of bees in study fulfills one's obligations to the parameters of quality according to the Codex |alimentariuses, e s carried out the manufacture of a tooth paste and a dental gel as the basic ingredients honey of bees as beginning active, according to the organoleptic characteristics and physicochemistries of both elaborate products, demonstrate be of good quality, demonstrated major viscosity in the tooth paste and smaller in the dental gel and by comparing the characteristics of quality between both products; the dental gel presents better aspect, better flavor and better refreshing sensation when applying .